2021
DOI: 10.1016/j.asmr.2021.01.022
|View full text |Cite
|
Sign up to set email alerts
|

No Significant Difference Between Intramedullary and Extramedullary Button Fixation for Distal Biceps Brachii Tendon Rupture After Cyclic Loading in a Cadaver Model

Abstract: To biomechanically compare intramedullary (IM) versus extramedullary (EM) distal biceps button fixation under cyclic loading conditions, which is most representative of postoperative physiologic status. Methods: This controlled laboratory study used 13 fresh-frozen matched paired cadaver elbows. One specimen from each pair was randomized to either IM (unicortical) or EM (bicortical) distal biceps button fixation via onlay technique. A servohydraulic actuator was used to cycle each specimen from full extension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…Unicortical drilling and intramedullary placement of fixation devices have demonstrated similar or better biomechanical properties in distal biceps repair pullout strength compared to bicortical drilling and extramedullary button placement, 8 and intramedullary all-suture anchors have demonstrated equal or superior fixation strength compared to intramedullary button. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Unicortical drilling and intramedullary placement of fixation devices have demonstrated similar or better biomechanical properties in distal biceps repair pullout strength compared to bicortical drilling and extramedullary button placement, 8 and intramedullary all-suture anchors have demonstrated equal or superior fixation strength compared to intramedullary button. 9 …”
Section: Discussionmentioning
confidence: 99%
“…It has been further validated in several biomechanical studies demonstrating equivalent and in some cases, superior biomechanical strength than suture anchor and extramedullary button fixation. 6 , 7 The greatest advantage of this revision technique is a safe and effective method to use the original intramedullary buttons. This technique could also be performed in other areas of the body where cortical button fixation is utilized such as a revision proximal biceps tenodesis or revision pectoralis major tendon repair.…”
Section: Discussionmentioning
confidence: 99%
“…Previous biomechanical studies determined that an intracortical suture anchor construct reduced gap formation by 25% to 47% when compared with the extracortical SB construct, pointing to increased tendon stability at the bicipital tuberosity in the presence of 2 points of tendon fixation. 27,37 Another advantage of the anatomic DB technique is the fact that it follows an onlay repair principle, which allows for appropriate tensioning of the tendon onto the tuberosity, as opposed to various inlay techniques that require insertion of the tendon into approximately 1 cm of the bone, with button fixation on the far cortex of the radius. 3 Ultimate tensile load is indicative of the capacity of a construct to withstand large muscle contractile loads.…”
Section: Discussionmentioning
confidence: 99%
“…Button pullout, secondary to fracture avulsion, was the primary mode of failure in the anatomic DB group of the present study. Majumdar et al 27 identified elongation and radial fracture to account for 10 of 13 DB construct failures. Siebenlist et al 37 noted that 58% (7 of 12) of intracortical DB constructs failed by fracture avulsion, lower than the 78% (7 of 9) of constructs failing in the same manner in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation